The everything war : Amazon's ruthless quest to own the world and remake corporate power - Mattioli, Dana (Little, Brown and Company, 2024)
"In 2017, Lina Khan published a paper that accused Amazon of being a monopoly, having grown so large, and embedded in so many industries, it was akin to a modern-day Standard Oil. Unlike Rockefeller's empire, however, Bezos's company had grown voraciously without much scrutiny. In fact, for over twenty years, Amazon had emerged as a Wall Street darling and its "customer obsession" approach made it indelibly attractive to consumers across the globe. But the company was not benevolent; it operated in ways that ensured it stayed on top. Lina Khan's paper would light a fire in Washington, and in a matter of years, she would become the head of the FTC. In 2023, the FTC filed a monopoly lawsuit against Amazon in what may become one of the largest antitrust cases in the 21st century."--Amazon.